Integrating strip cropping with grass border enhances soil fertility, maize grain, and nutritional yields in Zimbabwean smallholder farming systems - Madembo, Connie; Baudron, Frédéric; Mashingaidze, Arnold Bray; Murungweni, Chrispen; Bangira, Courage; Muoni, Tarirai; Thierfelder, Christian (Elsevier, 2025)
Smallholder maize production in sub-Saharan Africa is constrained by soil fertility decline and erratic rainfall, leading to low dietary diversity. A four-season on-farm study (2018/2019–2021/2022) was conducted with six farmers in Murehwa District, Zimbabwe, to evaluate the effects of maize–legume strip cropping on soil nutrient dynamics, crop yield, and total system nutritional yield. The experiment was a 2 × 6 factorial arranged in a split-plot randomized complete block design, comparing sole maize with maize strip-cropped with pigeonpea (Cajanus cajan (L.) Mills), cowpea (Vigna unguiculata L. Walp.), lablab (Lablab purpureus (L.) Sweet), velvet bean (Mucuna pruriens (L.) DC), and groundnut (Arachis hypogaea L.), with and without Brachiaria ssp. (cv. Mulato II (CIAT36087) grass border. Rainfall ranged from 495 to 1053 mm, influencing crop and soil responses. Strip cropping affected soil properties between the 2020/21 and 2021/22 seasons, notably pH, exchangeable potassium (K), and soil organic carbon (SOC). Maize + cowpea improved K (+65 %) and pH (+30 %), while maize + groundnut improved SOC (+5 %). Maize grain yield was strongly influenced by season and its interaction with the strip cropping system. Maize + velvet bean yielded 2.4 t ha−1 in 2018/19 and 2020/21, although sole maize produced the highest overall yield (3.2 t ha−1). Maize + pigeonpea consistently produced the highest grain yield among legumes (≈1.0 t ha−1) and total system protein yield (>0.3 t ha−1), while starch yield was highest under sole maize in 2020/21. Overall, maize-legume strip cropping, particularly pigeonpea, cowpea, and groundnut, improved system-level nutrient yield and selected soil properties, demonstrating its potential for climate-resilient smallholder farming.